Dual Identity and Prejudice: The Moderating Role of Group Boundary Permeability - Shi, Yuanyuan; Dang, Jianning; Zheng, Wenwen; Liu, Li (Frontiers in Psychology, 2017)
Past work suggested that dual identity was effective to reduce prejudice. This study extends research on dual identity and prejudice by identifying a boundary condition in this relationship, that is, group permeability. In Study 1, we replicated previous studies with Chinese individuals and found that inducing a dual identity (emphasizing subgroup differences and a common nation identity), compared to a control condition, decreased the urban residents’ prejudice against rural-to-urban migrants. In Study 2, we manipulated the group boundary permeability using the Hukou system reform, and found that when the group boundary was permeable, dual identity was effective in reducing prejudice against rural-to-urban migrants. However, this effect vanished in the condition where the group boundary was impermeable. These results point to the importance of inducing dual identity under specific conditions for research on decreasing prejudice. Some practical implications of the findings for urbanization and immigration are discussed.